The Kangaroo Hunters; Or, Adventures in the Bush - Bowman, Anne, active 19th century (Salt Lake City, UT : Project Gutenberg, 2013)
"The Kangaroo Hunters; Or, Adventures in the Bush" by Anne Bowman is a novel written in the mid-19th century. The story revolves around the Mayburn family, led by a grieving rector, Mr. Mayburn, after the death of his wife, and their journey to India as they take on a mission to minister to and educate the locals. The narrative explores the challenges they face, including their relationships with orphans, their encounters with diverse cultures, and the struggles of adapting to a new life in a foreign land. At the start of the story, the characters are introduced in the context of their domestic lives in Wendon, where Mr. Mayburn grapples with his sorrow and indecision after losing his wife while also considering his next steps as a rector. His conversation with Captain O'Brien highlights his emotional turmoil and the weight of responsibility towards his children and the orphans Ruth and Jack Martin, whom he$1 (Bs promised to care for. As the Mayburn family prepares to embark on their voyage, the narrative emphasizes the bonds formed among them, their growth, and the uncertainty of their future in a distant land filled with both promise and peril. The vibrant relationships and dynamic characters set the stage for an adventurous tale full of misfortune, resilience, and discovery. (This is an automatically generated summary.)s
Release date is 2013-08-14
E-text prepared by sp1nd, Mary Meehan, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Animals -- Juvenile fiction; Siblings -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Natural history -- Juvenile fiction; Survival skills -- Juvenile fiction; Kangaroos -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Frontier and pioneer life -- Juvenile fiction; Prisoners -- Juvenile fiction; Australia -- Description and travel -- Juvenile fiction